Hypertensive Pregnancy Disorders and Lipid Profiles: A Cohort Study: - Zare, Marjan; Faraji, Azam; Razavi, Behnaz (Galen Medical Journal, 2022)
Background: The global prevalence of hypertensive pregnancy disorders (HPDs) is 5.2%-8.2%. Lipid profiles made up of triglycerides (TG), total cholesterol (TC), low-density lipoprotein-cholesterol (LDL), and high-density lipoprotein-cholesterol (HDL) could affect the arterial vessel wall leading to HPDs. Preeclampsia (PE), among the most severe maternal-fetal HPDs, has affected 0.2%-9.2% of all pregnancies. The current study aimed to investigate the role of lipid profiles in predicting PE in the first and early third trimesters of pregnancy. Material and Method: A large-scale prospective cohort study was conducted from early pregnancy onward in a normal population in the south of Iran. Fasting blood samples were examined for TG, TC, HDL, and LDL, as well as LDL/HDL ratio levels in the first and early third trimesters. Result: Of 486 pregnant women, 37 women developed HPDs, of which 20 (54%) developed PE. In the PE group, the levels of serum lipid profiles, including TG, TC, LDL, and HDL, significantly raised with gestational age (P<0.05). After adjusting for maternal age and body mass index, TG, TC, LDL, and LDL/HDL ratio levels were associated with a higher risk of PE (odds ratio [OR]=1.025, 1.035, 1.03, 2.08, and 1.026, 1.044, 1.03, 2.14, P<0.001) regarding the first and early third trimesters, respectively. The optimum cut-off points for TG, TC, LDL, and LDL/HDL ratios predicting PE were estimated to be 180.5 mg/dl, 197.5 mg/dl, 136 mg/dl, and 3.66 in the first, and 220 mg/dl, 204 mg/dl, 155.5 mg/dl, and 3.97 in the early third trimesters. Conclusion: Dyslipidemia during pregnancy may help predict PE development that can be sustained with lipid-lowering drugs. [GMJ.2022;11:e2395]